Targeting DNA repair and hypoxia to improve radioresponse in breast cancer - Aiyappa, Radhika (2020)
Radiotherapy is an essential treatment modality in the clinical management of breast cancers, with an established role to reduce the risk of local recurrences. However, the repair of radiotherapy-induced DNA damage by cancer cells and the presence of tumour hypoxia reduces the efficacy of radiotherapy as a treatment modality. The present study aimed to assess how agents targeting DNA repair and hypoxia can modulate radioresponse in breast cancer. The aim of the current thesis was to investigate the single agent and radiosensitising efficacy of the FEN-1 inhibitor PTPD, and novel hypoxia-activated prodrug (HAP) KP167, in luminal and triple negative breast cancer models.